Embryonic background risk promotes the survival of tadpoles facing surface predators - Crane, Adam L. (PLoS One, 2018)
Exposure to intense predation risk can induce morphological and behavioural phenotypes that prepare prey, often at young ages, for surviving attacks from unknown predators. However, previous studies revealed that this survival advantage depended on the predator species. Here, we used alarm cues from injured conspecifics to simulate a period of high predation risk for embryonic wood frogs, Lithobates sylvaticus. Two weeks post-hatching, we tested whether the embryonic risk exposure influenced survival in encounters with two novel predators: (1) a spider (Dolomedes sp.) that ambushes prey exclusively on the surface of the water, and (2) the adult predacious diving beetle (Dytiscus sp.) which displays underwater sit-and-wait posture and pursuit tactics. Tadpoles exposed to embryonic high-risk survived longer when encountering spiders, whereas background risk had no influence on survival with adult beetles. These findings, coupled with survival studies involving other predator types, indicate that a high-risk environment promotes tadpole survival in future encounters with unknown sit-and-wait predators, but at the cost of increased vulnerability to novel predators capable of active pursuit.